Kearifan Lokal, Tradisi Pesantren, dan Masalah Toleransi Beragama di Indonesia - Murtado, Ramdan Zainal (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
This research was conducted to find out the local wisdom of Islamic boarding schools which become the solution to religious intolerance attitude in Indonesia. This research employed qualitative research by means of the library research method. The literature review is an important point in this research because that was where the researcher was able to collect information that becomes a reference for finding the phenomenon that occurs. An extraordinary gift was given by the Almighty when Indonesia has a diversity of cultures, ethnicities, languages, and religions. With the diversity that exists, it is undeniable that there are differences that lead to divisions and disputes, especially in religious differences. There is often occur an attitude of religious intolerance that becomes a public discussion, or within religion itself the occurrence of intolerance, because of different understandings in interpreting teaching he adheres to. This can lead to conflict in the community. Hence, this intolerance must be fixed by providing a universal understanding to the adherents of their respective religions. So that people do not fail to understand in understanding the teachings they profess. This difference must be upheld because the philosophy of religious life in Indonesia is oriented to Pancasila (Five Principles of the Indonesian State), as stated in the first principle, namely